Strategies for Teaching Arabic Language And Its Impact on the Development of Writing Skills At Ibn Sina University of Education Sciences Kepanjen Malang/استراتيجيّات تعليم اللّغة العربيّة وأثرها في تنمية مهارة الكتابة في جامعة ابن سينا لعلوم التربية كفانجين مالانق - Ilman Fahmi (Nurul Jadid University, 2018)
Writing is an important skill of language skills. Writing ability is also an essential goal of learning a foreign language. To achieve the desired goals, Arabic needs an effective and proportionate learning strategy for students' ability. Ibn Sina University for Education Sciences Kepanjen is one of the universities in which the Department of Arabic Language Education in Malang and with it the subjects that promote the skill of writing. Students learn these subjects in 3 semesters from the fifth through the seventh. Therefore, the teacher or teacher must use a positive strategy so that students do not feel bored. The researcher used the qualitative research approach and the descriptive approach. The result is that there are a number of strategies that contribute to the improvement of the process of teaching Arabic at Ibn Sina University for the sciences of education, especially in the skill of writing. These strategies are the PAKEM strategy in which the Guided Composition strategy, the Pragraf Building strategy and the Power of Two strategy have promoted the interest of students in the writing skill lesson.تعتبر الكتابة مهارة مهمة من مهارات اللغة. كما تعتبر القدرة على الكتابة هدفا أساسيا من أهداف تعلم اللغة الأجنبية. وللوصول إلى الأهداف المرجوة، تحتاج اللغة العربية إلى استيراتيجية تعليمها الفعال والمتناسب بقدرة الطلاب. جامعة ابن سينا لعلوم التربية كبنجين هي من إحدى الجامعات التي فيها قسم تعليم اللغة العربية في مالانق ومعها المواد الدراسية التي ترقي مهارة الكتابة. يتعلم الطلاب تلك المواد الدراسية خلال 3 فصول منذ فصل الخامس حتى فصل السابع. فلذلك لا بد على المعلم أو معلمة أن يستخدم استيراتيجية جذابية لكي لا يشعر الطلاب بالملل. واستخدمت الباحثة مدخل البحث الكيفي والمنهج الوصفي، وخرج بالنتائج هي: أن هناك مجموعة من الاستراتيجيات التي تسهم في إنجاج عملية تعليم اللغة العربية في جامعة ابن سينا لعلوم التربية خاصة في مهارة الكتابة. وتلك الاستيراتيجيات هي إستيراتيجية PAKEM التي فيها استيراجية Guided Composition واستيراتيجية Paragraf Building واستيراتيجية The Power of Two وكانت تلك الاستيراتيجية تسبب ترقية اهتمام الطلاب في درس مهارة الكتابة.